Screening and diagnosis of gestational diabetes: a hybrid method - Zalapa-Rios, Rene; Zalapa-Gómez, Maria Fernanda; Martinez-Cortes, Victor (International Journal of Research in Medical Sciences, 2023)
Background: In Mexico the gestational diabetes prevalence varies between 4 and 13%. The main purpose of this study is to determine the prevalence of gestational diabetes, the relevance of its risk factors, and its repercussions in pregnancy with a hybrid diagnostic method. Methods: This prospective, longitudinal, and observational study includes 347 pregnant women. Screening for gestational diabetes was performed with the O’Sullivan test, with a cut-off point of 140 mg/dL of glucose, followed by a 75-gram oral glucose tolerance test in patients with an abnormal screening test. The diagnosis was made with one or more abnormal results. Different variables were evaluated in these patients; from risk factors, to complications of gestational diabetes. Results: Of the 347 patients studied, 77 (22.2%) had a positive screen and 34 patients were confirmed with gestational diabetes (9.8%). A body mass index greater than or equal to 25 increased the relative risk by 2.52, the history of macrosomia by 4.10, a maternal age greater than or equal to 36 years by 2.54, and the presence of a twin pregnancy by 6.94. Regarding complications, there was an increase in prevalence of macrosomia (RR=4.09). Conclusions: The prevalence of gestational diabetes, using the combination of the two existing classical methods, is similar to that reported in other national and international studies, while also avoiding overdiagnosis, over-monitoring, and reducing typical discomforts that may come by using the one-step method.